Thyroid Scintigraphy and Therapy in the Setting of Hyperthyroidism: Review of a "Hot" Topic - Daniel Glazer; Hatice Savas; Richard Brown; Ka Kit Wong; Ancaa Avram; Milton Gross (Association of American Medical Colleges, 2014)
Abstract This is an interactive module aimed at senior medical students and radiology residents during a nuclear medicine rotation that discusses the common imaging findings of conditions that cause hyperthyroidism. Typical cases of Graves disease, Plummer disease, toxic multinodular goiter, and thyroiditis are presented in an interactive fashion using illustrative case examples accompanied by multiple-choice questions. Issues that arise following radioiodine therapy with regard to Nuclear Regulatory Commission rules, and causes and mechanisms of iodine-induced hyperthyroidism and hypothyroidism are also discussed. It is anticipated that an individual will go through the presentation in a self-guided manner. It will likely take approximately 1 hour to complete the entire presentation. While this basic presentation should suffice for medical students and junior residents, it is not meant to be a definitive source of facts for more senior radiologists. Those that require more in-depth information can utilize some of the selected resources listed at the end of the presentation or consult a nuclear medicine textbook. Because of the question and answer format, it is hoped that this presentation will be useful for medical students, radiology residents, and even practicing radiologists as a review tool.